Penanganan Bencana Erupsi Gunung Sinabung Ditinjau dari Aspek Komunikasi dan Koordinasi - Fatma Wardy Lubis; Yovita Sabarina; Munzaimah Masril (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2019)
This study aims to determine how disaster management is carry out by the government and stakeholders in dealing with the Mount Sinabung Eruption disaster, especially in the mitigation phase. By using the Qualitative Method, data collection was done through in-depth interviews, Focus Group Discussion (FGD) and Observations to get an overview of the handling of the Mount Sinabung Eruption in terms of two aspects; Communication and Coordination. The FGD was held in three locations; Simacem, Bekerah, and Sukameriah Villages, while FGD participants involved three categories; teenagers, women and men. The results showed that the eruption victims did not receive adequate communication regarding the knowledge of the Mount Sinabung Eruption disaster, both from the government and other organizations outside the government, even though in the mitigation phase awareness efforts should be made to the community through counseling, training, mentoring and inputting topics about the eruption of Mount Sinabung in the learning curriculum in schools ranging from kindergarten to senior high school, as well as conducting regular training. However, the training was not carried out as a result of the eruption victims had no preparation, guidelines and did not know the anticipatory measures in the face of Mount Sinabung every time an eruption occurred, while this eruption could not be ascertained when it will end. Until now there has been no organized and permanent coordination between the government and community groups outside the government, so that disaster management is still carried out spontaneously without any specific guidelines for inter-agency coordination..